Altered High Density Lipoprotein Composition in Behavioral Variant Frontotemporal Dementia - Kim, Woojin Scott; He, Ying; Phan, Katherine; Ahmed, Rebekah M.; Rye, Kerry-Anne; Piguet, Olivier; Hodges, John R.; Halliday, Glenda M. (Frontiers in Neuroscience, 2018)
Frontotemporal dementia (FTD) is a common cause of early onset dementia with behavioral variant FTD (bvFTD) being the most common form. bvFTD is characterized clinically by behavioral and personality changes, eating abnormalities, and pathologically, by systemic lipid dysregulation that impacts on survival. As lipoprotein metabolism is at the core of lipid dysregulation, here, we analyzed the composition, both proteins and lipids, of the two major lipoprotein classes in blood – high density lipoproteins (HDLs) and low density lipoproteins (LDLs). Fasted plasmas from bvFTD and Alzheimer’s disease (AD) patients and controls were fractionated using fast protein liquid chromatography (FPLC) and samples analyzed by lipid assays, ELISA and western blotting. We found that apolipoprotein A-I (apoA-I) and apolipoprotein A-II (apoA-II) levels in HDLs were decreased in bvFTD compared to controls, whereas apolipoprotein B (apoB) levels in LDLs were unaltered. We also found that cholesterol and triglyceride levels in FPLC fractions were altered in bvFTD compared to controls. The apoB:apoA-I ratio and the standard lipid ratios were significantly increased in bvFTD compared to AD and controls. Furthermore, we found that plasma apolipoprotein C-I and paraoxonase 1 levels were significantly altered in bvFTD and AD, respectively, compared controls. This study represents the first apolipoprotein analysis of bvFTD, and our results suggest altered HDL function and elevated cardiovascular disease risk in bvFTD.